Afghanistan after the Western Drawdown (Rowman & Littlefield, 2015)
Al Qaeda, the Afghan Taliban, and their allies are poised to return to Afghanistan and the Mujahidin in Pakistan may once again draw the support of pools of fighters. Experts from the countries discussed explain the post-2014 key strategic decisions that face policymakers in Afghanistan, the United States, and the region